Civil rights as patient experience: How healthcare organizations handle discrimination complaints. Issue 2 (27th May 2021) - Kirkland, Anna; Hyman, Mikell
Abstract: The nondiscrimination clause of the Affordable Care Act, known as Section 1557, formally expanded patients' civil rights in nearly every healthcare setting in the United States in 2010. Regulations required healthcare organizations to name a person to handle grievances and set up an internal grievance process for resolving them. Drawing on interviews with 58 healthcare grievance handlers, this study examines how healthcare organizations respond to patients' discrimination complaints. We find that organizations incorporated the new right into preexisting complaint and grievance procedures, treating possible patient civil rights violations as patient experience problems. Grievance handlers smooth over problems using customer service strategies. These procedures diminish the efforts of policymakers to expand civil rights protections in healthcare. For civil rights to provoke real organizational change, discrimination complaints would need to be handled by professionals attuned to rights consciousness.